The value of pre-operative magnetic resonance cholangiopancreatography (MRCP) in assessment of patients undergoing cholecystectomy - Mohammed Ahmed Mohammed Badr; Maryse Youssef Awad Allah; Mohammed Hassan Fahmey; Reda Saad Abdullatif (Cairo : Mohammed Ahmed Mohammed Badr, 2016)
For the patients undergoing cholecystectomy, it is important for surgeons to have detailed preoperative imaging data about anatomy and variations of gall bladder as well as biliary tract for each patient. It is also important to determine the nature (benign or malignant) and level (gall bladder, intrahepatic biliary radicals, extrahepatic biliary radicals, hepatic, pancreatic or duodenal) pathologies. The previously mentioned preoperative data are helping the surgeons to minimize (up to preventing) the post operative complications. MRCP is non invasive technique that plays an important role in detection of these detailed preoperative imaging data
Thesis (M.Sc.) - Cairo University - Faculty of Medicine- Department of Radio-diagnosis
Issued also as CD
Keywords: Anatomical variations of biliary tree; Cholecystectomy; MRCP